2008
DOI: 10.1007/s10311-007-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the levels and sources of trace elements in urban particulate matter

Abstract: An assessment of air quality of Belgrade, Serbia, was performed by determining the trace element content in airborne daily PM 10 and PM 2.5 samples collected from a central urban area. The ambient concentrations of Zn were the highest in PM 2.5 (1,998.0 ng m -3 ). Multivariate receptor modelling (principal component analysis and cluster analysis) has been applied to determine the contribution of different sources of specific metallic components in airborne particles. The obtained results showed that vehicle tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 15 publications
3
32
0
1
Order By: Relevance
“…The higher enrichment of elements in Centro by non-crustal sources could be explained by either industrial activities, since Cd comes from metallurgical processes [43], or traffic, because Zn and Pb are markers of vehicular emissions [44]. In urban areas, road traffic (diesel engines and brake wear) could be the most important source of Cu [45]. Conversely, an earlier study suggested that geological sources significantly influenced the generation of PM 2.5 as much in Miravalle as they did in Centro [27].…”
Section: Metals In Pm 25mentioning
confidence: 99%
“…The higher enrichment of elements in Centro by non-crustal sources could be explained by either industrial activities, since Cd comes from metallurgical processes [43], or traffic, because Zn and Pb are markers of vehicular emissions [44]. In urban areas, road traffic (diesel engines and brake wear) could be the most important source of Cu [45]. Conversely, an earlier study suggested that geological sources significantly influenced the generation of PM 2.5 as much in Miravalle as they did in Centro [27].…”
Section: Metals In Pm 25mentioning
confidence: 99%
“…For calibration, standard solutions containing all metals of interest were prepared using Merck certified atomic absorption stock standard solutions containing 1000 mg l -1 metal in 0.5 N HNO3 and Milli-Q quality deionised water, with no matrix modifier addition. Details on sampling procedures and PM analysis are given in detail elsewhere [50][51][52][53][54][55].…”
Section: Experimental Methods and Proceduresmentioning
confidence: 99%
“…Like in many other major cities with a few millions inhabitants, of the primary sources, fossil fuel combustion and traffic contributions play the most significant role [51].…”
Section: Weekend Effect and Pm10 Temporal Variationsmentioning
confidence: 99%
“…Although Minguillòn et al (2012) stated high Pb concentrations might be related with thermal processes, they also concluded a factor associated with Zn and Cu from road traffic. V and Ni are considered to be the markers of oil combustion (Rajšić et al, 2008). Emission sources of Hg have been extensively investigated and classified into coal combustion, solid waste incinerators, steeling industries, mobile sources, and wildfires ( Landis et al, 2007;Choi et al, 2008;Huang et al, 2010;).…”
Section: Introductionmentioning
confidence: 99%
“…However, the required inputs for this kind of model shows high uncertainty and a complicated calculate scheme is required for application (Byun and Ching, 1999). Nevertheless, a simple and low cost receptor model could be applied to identify the origins of plumes, such as principal component analysis (PCA), coupled with Hybrid Single Particle Lagrangian Integrated Trajectory Model (HSYPLIT) and/or conditional probability function (CPF) (Rajšić et al, 2008;Huang et al, 2010;Cheng et al, 2012). For example, Rajšić et al (2008) identified that the particulate matter observed high of Zn, Mn, Fe, and Al was from road dust, while V and Ni were emitted from oil combustion, and Cu, Cd, and Pb were linked to mobile sources by applying PCA to indentify emission sources of trace metals.…”
Section: Introductionmentioning
confidence: 99%